Influence of Social Confinement by Covid-19 on Air Quality in the District of San Juan De Lurigancho in Lima, Peru - Camila A. Medina Leon; Mercy F. Meza Felix; Carlos A. Castaneda Olivera (Chemical Engineering Transactions, 2022)
During the pandemic, citizens were immobilized and different anthropic activities were paralyzed, reducing contamination by vapor and gas emissions, and consequently improving air quality. Therefore, this research evaluated the influence of social confinement (from March to May) by COVID-19 on air quality in the district of San Juan de Lurigancho (SJL) in Lima, Peru. Data on pollutants (PM2.5, SO2 and O3) were obtained from the National Service of Meteorology and Hydrology (SENAMHI). The results showed that in 2019, before the social confinement, pollutants PM2.5, SO2 and O3 had average maximum values of 75.79, 22.97 and 22.94 µg/m3, respectively. In the year 2020, during the social confinement, pollutants PM2.5 and SO2 had a significant reduction, with average minimum values of 14.09 and 11.26 µg/m3, respectively. Meanwhile, O3 gas increased to 17.35 µg/m3. After the quarantine, in the months of June to December 2020, a progressive increase in the concentration of pollutants was seen as industrial and vehicular transport activities were reestablished. Finally, it is concluded that social confinement by COVID-19 improves air quality and shows that urban control measures should be taken to reduce the concentration of air pollutants.